Designing an ESP Speaking syllabus for the second-year students of Marine Engine Department at Maritime College No.I - Nguyễn, Thị Minh Thái (University of Languages and International Studies, 2017)
Chapter 1 provides an overview of syllabus design, ESP and speaking skill. Chapter 2 presents a small research on MCI students' needs to learn English in general and speaking skills in particular. Then it focuses in the presenting and discussing on how the ESP speaking syllabus for second-year students of Marine Engine Department at MCI is designed.